AS PROPOSIÇÕES DO ENFOQUE CTS NOS LIVROS DIDÁTICOS DE CIÊNCIAS DO 9º ANO - Cortez, Jucelino (2020)
This article presents the results of a qualitative research with the didactic books included in the National Plan of the Didactic Book of the discipline of Physics of the 9th year of elementary education, used in the city of Passo Fundo, northern region of Rio Grande do Sul. Of this work is focused on the analysis of the forms and dispositions with which the contents are presented and worked on in these books, trying to identify in which opportunities proposed by the works can identify the presence of the vocations of the STS approach. In this way, it is also intended to offer, to managers and teachers of basic education, subsidies when choosing this tool. With the research, we identified, through the unveiling of categories, how and when such vocations are identified, according to the theoretical framework used in this study.